Band Offsets of Insulating & Semiconducting Oxides on (AlxGa1-x)O3. (3rd July 2019) - Fares, Chaker; Kneiss, Max; von Wenckstern, Holger; Grundmann, Marius; Tadjer, Marko J; Ren, Fan; Hays, David; Gila, Brent P; Pearton, Stephen J.
Abstract : There is a growing interest in (Alx Ga1-x )2 O3 /Ga2 O3 heterostructure devices for use in power and rf electronics. For these heterostructures, wide bandgap oxides can be used as gate dielectrics, and narrow energy band gap conductive oxides can be utilized to reduce contact resistance between the Ohmic contacts and semiconductor surface. In this study, we utilize x-ray photoelectron spectroscopy (XPS) to report on the determination of the band alignment of various insulating and semiconducting dielectrics onto (Alx Ga1-x )2 O3 as a function of aluminum concentration. The dielectrics were deposited using atomic layer deposition (ALD) or sputtering. For SiO2 and Al2 O3, there are differences of up to 1 eV in band alignments on single crystal (Alx Ga1-x )2 O3, depending on the deposition method. For both of the conductive oxides, AZO/ β-(Alx Ga1-x )2 O3 and ITO/ β-(Alx Ga1-x )2 O3, the valence and conduction band offsets were negative and can be used to enhance carrier transport across the heterointerface.